2019
DOI: 10.1534/g3.118.200763
|View full text |Cite
|
Sign up to set email alerts
|

High Level of Conservation of Mitochondrial RNA Editing Sites Among Four Populus Species

Abstract: RNA editing occurs in the endosymbiont organelles of higher plants as C-to-U conversions of defined nucleotides. The availability of large quantities of RNA sequencing data makes it possible to identify RNA editing sites and to quantify their editing extent. We have investigated RNA editing in 34 protein-coding mitochondrial transcripts of four Populus species, a genus noteworthy for its remarkably small number of RNA editing sites compared to other angiosperms. 27 of these transcripts w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
30
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(33 citation statements)
references
References 59 publications
3
30
0
Order By: Relevance
“…As a post-transcription process, RNA editing can modify the genome template to produce a different transcript [13]. Significant progress has been made in recent years in RNA editing studies for plant, numerous studies have proved that RNA editing occurred in nearly all plants in the kingdom, and demonstrated that RNA editing played roles not only in abiotic stress tolerance but also likely in the plant development, such as flower development and male sterile [8, 9,14,19], RNA editing may also result in secondary structure transformation of transcripts [25]. Until now, there are two viewpoints about the nature of RNA editing, one is contribution to proteomic sequence variation, thus provide another mechanism for modulating gene expression; another point thinks that RNA editing in plants is a repair mechanism to correct genomic point mutations at RNA level and alter the substitutional rate that is extremely low in organellar genes [26,27].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…As a post-transcription process, RNA editing can modify the genome template to produce a different transcript [13]. Significant progress has been made in recent years in RNA editing studies for plant, numerous studies have proved that RNA editing occurred in nearly all plants in the kingdom, and demonstrated that RNA editing played roles not only in abiotic stress tolerance but also likely in the plant development, such as flower development and male sterile [8, 9,14,19], RNA editing may also result in secondary structure transformation of transcripts [25]. Until now, there are two viewpoints about the nature of RNA editing, one is contribution to proteomic sequence variation, thus provide another mechanism for modulating gene expression; another point thinks that RNA editing in plants is a repair mechanism to correct genomic point mutations at RNA level and alter the substitutional rate that is extremely low in organellar genes [26,27].…”
Section: Discussionmentioning
confidence: 99%
“…However, the prior approach is time-consuming and prone to underestimate editing sites and overestimate editing extent, because when comparing cDNA with genomic sequences for editing extent of less than 10%, one has to sequence more than 10 clones to find one edited transcript. With the advent of sequencing technology, the availability of large quantities of deep, strand-specific cDNA sequencing (RNA-seq) data offers a powerful technique to identify all the potential RNA editing sites and quantify their editing extent especially for the sites with very low extent, hence, RNA editing sites were identified in more and more organisms based on RNA deep sequencing [14,19,28].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…1). RNA editing sites were determined (16) using RNA-Seq data from fife ‘Börner’ tissues. A total of 133 genes with 90 editing sites were identified for cp_Boe, encoding 85 mRNAs, 39 tRNAs, 8 rRNAs and 1 pseudogene.…”
Section: Figmentioning
confidence: 99%
“…However, no instance of RNA editing has yet been detected in Marchantiidae and algae, suggesting that RNA editing may have evolved in organelles only after the green plants established themselves on the land [6]. Many excellent studies in different plants have recently appeared and described their mechanistic and functional aspects [14][15][16]. The frequency of organellar RNA editing varies from zero to thousands of sites across plant kingdom, among land plants.…”
Section: Introductionmentioning
confidence: 99%